Baby beds’ sleep micro-environment in day care centres - Zeiler , Wim (CLIMA 2022 conference, 2022)
Concerns are emerging about potential adverse effects of indoor air pollutants on children's health and development, since young babies are exceptionally more sensitive to chemical exposures than children and adults. Day care centres (DCCs) are the most important place besides their home as babies spend up to 11 hours inside the DCCs, of which half of the time in their beds during the first six months. Especially during the first year their developing lungs are highly sensitive to pollutions. Ventilation within the baby bed themselves is rarely studied however insufficient IAQ conditions at DCCs were unanimously confirmed in t previous studies. Therefore, the main aim of this paper is to state the importance of improving the indoor air quality at day-care centres, especially in sleep micro-environment of the baby beds. The paper presents an overview to emphasize the importance for the health of babies.